Chalcogenide Ovonic Threshold Switching Selector - Zihao Zhao; Sergiu Clima; Daniele Garbin; Robin Degraeve; Geoffrey Pourtois; Zhitang Song; Min Zhu (Nano-Micro Letters, 2024)
Highlights The development history and key milestones of ovonic threshold switch (OTS) materials were comprehensively summarized. Combined with the latest advancements of OTS research, the mainstream OTS material systems were systematically introduced. A thorough overview of the prevailing viewpoints regarding the OTS switching mechanisms was presented. Recent progress in OTS devices for applications in 3D memory, self-selecting memory, and neuromorphic computing was summarized.